Faith : taking flight - Murphy, Julie, 1985- ([Faith Herbert Origin Story, 2020)
"When she's not hanging out with her two best friends, Matt and Ches, Faith Herbert is volunteering at the local animal shelter or obsessing over the long-running teen drama The Grove. So far, her senior year has been spent trying to sort out her feelings for her maybe-crush Johnny and making plans to stay close to Grandma Lou after graduation. And there's the small matter of recently discovering she can fly. Then the fictional world of The Grove relocates to her town, and TV heroine Dakota Ash takes a romantic interest in Faith. But when animals, then people, begin to vanish, only Faith seems able to connect the dots to a new designer drug infiltrating her high school." -- Adapted from jacket.